Enhanced Control Efficacy of Different Insecticides Mixed with Mineral Oil Against Asian Citrus Psyllid, Diaphorina citri Kuwayama, Under Varying Climates - Wei Hu; Kejing Wang; Xiaoyue Zhong; Pei Jiang; Shunchang Zhang; Zhanjun Lu; Zhixiang Zhang; Long Yi; Ning Zhang (Insects)
Asian citrus psyllid (ACP), Diaphorina citri (Hemiptera: Liviidae), is one of the most devastating pests in citrus orchards due to its role in transmitting Huanglongbing (HLB). Currently, chemical control remains the most effective strategy for ACP management. Mineral oils are commonly used as insecticides or adjuvants in integrated pest management (IPM) practices. To extend the product life of synthetic pesticides, we evaluated the toxicity of chlorpyrifos (CPF), thiamethoxam (THX), or pyriproxyfen (PPF) mixed with mineral oil Lvying (LY) against ACP nymphs under different weather conditions. Individual application of CPF, THX, and PPF effectively controlled against ACP nymphs under no rain conditions, with mortality rates varying from 20 to 100% during 1–5 d after treatment. The addition of LY at 1.0% or 0.5% rates to CPF, THX, and PPF significantly enhanced their control efficacy, achieving sustained mortality rates from 60 to 100% during the same period. Light rain had less impact on the control efficacy of these insecticide mixtures compared to individual insecticides. However, cumulative rainfall above 20 mm significantly reduced the control efficacy of individual insecticides and their mixtures. The addition of LY decreased both surface tension and contact angle of THX solution on citrus leaves, thereby enhancing the solution’s wetting and increasing THX deposition. Moreover, the rainfastness of THX was improved after adding LY, leading to a greater retention on the leaves. LY at a rate of 1.0% exhibited excellent efficacy against ACP nymphs, and observations using scanning electron microscopy (SEM) showed that LY altered ACP mouthpart morphology and blocked spiracles, likely contributing to its insecticidal effects. This study revealed that mineral oils can serve as both insecticides to combine with synthetic pesticides for enhancing toxicity against ACP and as adjuvants to facilitate the deposition and rainfastness of synthetic pesticides on leaves, which could be recommended for sustainable ACP management in citrus orchards.